Tafsir Maqāṣidī in Responding to the Issue of Marriage with People of the Book: Conceptual, Analytical Study, and Contemporary Relevance - Ahmad Hidir Amin; Khairil Anwar; Taufik Warman Mahfuzh (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study examines verses on marriage with Ahlul Buku through a maqāṣidī interpretation approach in an effort to present a more comprehensive, adaptive, and relevant understanding of contemporary social dynamics. This study is important because the issue of interfaith marriage continues to be debated in Islamic legal discourse and modern family regulations, while many classical readings tend to focus on the literal meaning of the text without considering the objectives of Sharia and the current social context. This study aims to explain the basic concepts of maqāṣidī interpretation, analyze related verses, and assess their relevance and implications in pluralistic family life. The research method is qualitative with a literature review approach, using maqāṣidī steps including verse identification, linguistic and historical context analysis, maqāṣid determination, maslahat-mafsadah evaluation, and formulation of legal recommendations. The results show that the permissibility of marrying Ahlul Buku is conditional and must consider the social impact, protection of faith, and family sustainability. The maqāṣidī approach offers a more proportional answer by placing justice, benefit, and family protection as the main principles. This study recommends strengthening the maqāṣid methodology in tafsir studies, drafting regulations that protect the rights of interfaith family members, and the need for comprehensive premarital education.